Implementation of a workplace protection system and its correlation with experiences of workplace violence: a cross-sectional study - Eun-Mi Baek; BoKim Lee (BMC, 2023)
Abstract Background While customer interactions are inherent and essential aspects of the service industry, instances of violence against service workers have brought social attention to the need for a system to ensure their protection. In South Korea, a protection system for the health of service workers has been implemented to prevent this type of violence and its negative consequences. This study conducted a comparative analysis to clarify the impacts of this protection system across a sample of service workers. We collected data on their general characteristics, occupational characteristics, and experiences with the service protection system to determine how those factors were related to workplace violence, with a focus on whether the system has reduced such occurrences. Methods We collected self-reported survey data over 28 days (March 2 to March 30, 2020), resulting in 1,349 (99.3%) responses for our final analysis. We conducted a chi-square test and logistic regression analysis to investigate the general and occupational characteristics, experiences of violence, and experiences with the worker protection system. Results We found workplace violence is more observed among males, older workers, electronic equipment repairers, irregular workers, and those who worked for extended periods. On the other hand, we found a reduction in the occurrence of workplace violence in businesses that provided service workers with regular counseling from professional counselors, had designated persons responsible for grievance procedures, and/or had grievance procedure committees. We found the lowest likelihood of workplace violence in businesses that operated stress relaxation programs (all p < 0.01). Conclusions This study identified a correlation between the adoption of the protection system for service workers and the prevalence of workplace violence. We also clarified the effects of the service protection system and developed a plan for its expansion. Key points This study clarified the correlation between the adoption of the protection system for service workers and the occurrence of workplace violence. Along with our investigation of the protection system's effects, these findings provide a basis for expanding Korea's existing worker protection system.